BS EN IEC 61009-2-2. Residual current operated circuit-breakers with integral overcurrent protection for household and similar uses (RCBO's). Part 2-2. RCBOs according to 4.1.2, 4.1.3, 4.1.4, 4.1.5 and 4.1.6 (3rd December 2020) - British Standards Institution,
No abstract available